ANALISIS YURIDIS PENCABUTAN KEKUASAAN WALI DAN PENGALIHAN PERWALIAN KEPADA NENEK DALAM KONTEKS PERLINDUNGAN HAK WARIS ANAK YATIM - Sari Maisyarah Damanik; Hasim Purba; Rosnidar Sembiring (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The Indonesian legal system pays special attention to the protection of orphans' rights in the context of guardianship and inheritance rights through various legal instruments such as the Marriage Law, the Compilation of Islamic Law, and the Child Protection Law. This normative legal research examines three main issues, namely the legal provisions on the revocation of guardianship and transfer of guardianship, the judge's legal considerations in Decision Number 57/Pdt.G/2024/PA.Pspk, and the legal implications of the decision on the protection of orphans' inheritance rights, using a statutory approach and a case approach. The results of the study indicate that the Indonesian legal framework has comprehensively regulated the revocation and transfer of guardianship, where judges use multiple perspectives in considering the transfer of guardianship from the biological father to the grandmother based on the negligence of the guardian, the ability of the substitute guardian, and the best interests of the child in the management of inheritance and Taspen, which has implications in the form of legal legitimacy for the grandmother as the new guardian, the obligation to record the child's assets, and a monitoring mechanism by the court, so that it is necessary to harmonize regulations, develop more detailed substitute guardian eligibility assessment standards, and establish a monitoring system for the management of children's inheritance. Keyword: Guardianship, Revocation and Transfer of Guardian, Inheritance Abstrak: Sistem hukum Indonesia memberikan perhatian khusus terhadap perlindungan hak-hak anak yatim dalam konteks perwalian dan hak waris melalui berbagai instrumen hukum seperti UU Perkawinan, Kompilasi Hukum Islam, dan UU Perlindungan Anak. Penelitian hukum normatif ini mengkaji tiga permasalahan utama yaitu ketentuan hukum tentang pencabutan kekuasaan wali dan pengalihan perwalian, pertimbangan yuridis hakim dalam Putusan Nomor 57/Pdt.G/2024/PA.Pspk, serta implikasi hukum putusan tersebut terhadap perlindungan hak waris anak yatim, dengan menggunakan pendekatan perundang-undangan dan pendekatan kasus. Hasil penelitian menunjukkan bahwa kerangka hukum Indonesia telah mengatur secara komprehensif mengenai pencabutan dan pengalihan perwalian, dimana hakim menggunakan multi-perspektif dalam mempertimbangkan pengalihan perwalian dari ayah kandung kepada nenek berdasarkan kelalaian wali, kemampuan wali pengganti, dan kepentingan terbaik anak dalam pengelolaan harta warisan dan Taspen, yang membawa implikasi berupa legitimasi hukum bagi nenek sebagai wali baru, kewajiban pembukuan harta anak, dan mekanisme pengawasan oleh pengadilan, sehingga diperlukan harmonisasi peraturan, pengembangan standar penilaian kelayakan wali pengganti yang lebih rinci, serta pembentukan sistem monitoring pengelolaan harta waris anak. Kata kunci: Perwalian, Pencabutan dan Pengalihan Wali, Waris